Upaya Penanggulangan Praktek Kejahatan Premanisme: Perspektif Sosio-Kriminologi - Ahmad Muzammil; M. Wahyu Aditya Pratama; Chareldo Satori; Dedi Irawan Pratama; Sobriadi (Consensus : Jurnal Ilmu Hukum, 2023)
In Indonesia, premanism, which is an act of social crime, is now a new culture. And since it has been a security tool when interests or positions are threatened, premanism always happens. Premanism stems from the desire to satisfy difficult needs, such as poverty, security, order, and freedom from threats. This urge can encourage people to act with a premanistic attitude. A pre-manist attitude is a culture or subculture divided by a dominant culture and difficult to eliminate repressively.